TRAINING ON ORGANIC WASTE PROCESSING AND PRODUCT BRANDING OF ORGANIC WASTE PROCESSED IN THE PEPELING COMMUNITY - Damastuti, Riski (Politeknik Negeri Jember, 2023)
Garbage is a never-ending problem. In Yogyakarta, the volume of waste generated by the community exceeds the capacity of the available TPST. One of the TPSTs that experienced an excess amount of waste was the Piyungan TPST. The Piyungan TPST, which should not have been used since 2005, is still being used today and always receives a very large amount of waste. This caused various rejections from the surrounding community because of the adverse impact on society. In this community service activity, socialization was carried out on processing household waste independently through maggot cultivation, as well as branding training to provide added economic value from maggot cultivation activities. Through this activity, partners are expected to be independent in waste processing and can become agents of change in waste management to the surrounding community